GENETIC EFFECTS IN CONTROLLING GRAIN FILLING DURATION IN WHEAT CROSSES - M. I. Khan; A. J. Khan; G. S. S. Khattak; F. Subhan (Journal of Animal and Plant Sciences, 2014)
Genetic effects for grain filling duration were determined in two bread wheat crosses (Bakhtawar-92 × Frontana: Cross-1; (Inqilab-91 × Fakhr-e-Sarhad: Cross-2) during 2006-07 and 2008-09. Joint segregation analysis (JSA), designed for six basic populations i.e. P1, F1, P2, BC1, BC2 and F2 was used as statistical approach. In both crosses, the grain filling duration was controlled by mixed additive and dominant effects of two major genes and several polygenes. Negative additive effects were found due to first and second major genes in the crosses during both years indicating that the major genes may affect the said trait adversely except in Bakhtawar-92 × Frontana during first year where the additive effect was positive due to the second major gene. However, the positive additive effects due to polygene were observed in the crosses during both years. Transgressive segregates for long and short grain filling duration indicated the dispersion of favorable and adverse genes in the parental genotypes. Major genes heritability for grain filling duration was higher than heritability due to polygene in BC1, BC2 and F2 for the crosses with highest environmental influence. Additive genetic effects of the major and polygene were pronounced thus selection of desirable recombinants for both short and long grain filling duration may be delayed till the accumulation of maximum favorable genes in the subsequent advance generations.
Keywords: Major genes + minor genes interaction— grain filling duration —Triticum aestivum L